The Sign Found in The Movie “Mr Harrigan’s Phone” - Ni Nyoman Puteri Antari; I Gusti Ngurah Adi Rajistha; A.A Istri Manik Warmadewi (CV. Tirta Pustaka Press, 2023)
The title of this research is “The Sign Found in The Movie Mr Harrigan’s Phone”. This research has difference with the other previous. Previous research was analyzing kind and function. This research analyzes types and meaning by Peirce and Barthes. Previous research used action, adventure, and fantasy movie genres. This reseach used horror and drama genres. The purpose of this research are observe and provide information to readers about the types and inform the meanings contained in the movie